Aquaponic analysis using the PV system - Tyassilva, Arfienda Miawa; Aripriharta, Aripriharta; Ihsan, Rifqi Al; Alfadel Saputra, Rui; Omar, Saodah; Ching, Hung-Yu (2023)
Aquaponics system is currently a trend among the people. Many communities are competing in the development of aquaponics systems. This is because the aquaponics system is a new and renewable energy development that is environmentally friendly. Utilization of solar energy as a source of electricity is one of the efforts to develop aquaponics system innovation. This concept is through energy from sunlight stored in solar panels and then converted into electrical energy for modern agricultural systems. This research involves a combination of electronics and agriculture as a sustainable system using solar panels, inverters, and water pumps. Solar panels are considered as an alternative in generating electricity, by producing an output voltage of 24V. The magnitude of this voltage value depends on the sunlight that is accommodated by the solar panel. Weather can affect the performance of solar panels in accommodating the amount of sunlight. The implementation of this project requires electrical energy from solar panels by utilizing an inverter to convert direct current (DC) into Alternative Current (AC) to increase the voltage from 24V to 220V.